Legislative Drafting and Climate Justice Aspects: An Evaluation of the Consistency of the Omnibus Law on Job Creation with Sustainable Development Principles - Henny Saida Flora; Cindy Mariam Magdalena Rantung; Shintia Alvernia Gorrettie Gijoh; Irsan Rahman; Samuel Frans Boris Situmorang (Inovasi Pratama Internasional. Ltd, 2026)
This study employs quantitative methods to evaluate the consistency of Indonesia's Omnibus Law on Job Creation (UU Cipta Kerja) with climate justice principles and sustainable development goals. Through statistical analysis of environmental licensing data, foreign direct investment flows, and ecological degradation indicators from 2019-2023, the research reveals significant regulatory simplification that potentially undermines environmental safeguards. The analysis demonstrates a 47.4% reduction in licensing procedures, correlating with increased investment but raising concerns about procedural justice and intergenerational equity. Panel data regression analysis indicates that while the law achieved its objective of improving investment climate, it simultaneously weakened environmental protection mechanisms, particularly through the replacement of environmental permits with environmental approvals. The findings suggest that the legislative drafting process prioritized economic efficiency over climate justice considerations, creating potential conflicts with constitutional mandates for environmental protection and Indonesia's commitments under the Paris Agreement. This research contributes empirical evidence to the discourse on balancing economic development with climate justice in emerging economies